Urgensi Sejarah Masuk dan Penyebaran Islam di Kawasan Asia Tenggara - Saputra, Dony (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Research on the Urgency of Historical Analysis of the Entry and Spread of Islam in Southeast Asia is the title of this study. The aim of this research is to characterize and evaluate how Islam spread throughout Southeast Asia. Through Arab trade, Islam entered Southeast Asia around 7 AD. It is worth mentioning that the eastern route was also used by the Malay culture to get to Indonesia between 300 and 200 BC, which eventually spread to various regions in the country. Words and sentences taken from many educational articles through analysis of the results are the data used in this research.